THE POTENTIAL OF THE ANTI-HEGEMONIC COALITION - Mihajlović, Dejan; Obradović, Zoran (The Policy of National Security, 2024)
The authors consider the potential of a loose coalition in curbing US global influence, ie. the implications of its formation and strengthening on the final establishment of multipolarity. Based on the view that international relations are increasingly defined by multipolarity and that the opposition is increasingly speaking out against yesterday’s hegemon, the authors point out that the US insists on an increasingly harsh global polarization, while Russia and China strive to initiate global “de-dollarization” mechanisms. The joining of African and Middle Eastern countries to the anti-American bloc initiates international processes that potentially lead to the strengthening of existing and the formation of new units of collective security. After a period of soft balancing of US power, in the period from the coming to power of the Putin administration until the conflict in Georgia in 2008, the Russian Federation began an era of hard balancing, and the conflicts in Syria and the current one in Ukraine are the best indicators. By intervening in Syria, Russia secured the supply of its own gas to Europe and regained its international reputation, while by launching military operations in Ukraine, it rejected immediate military threats to NATO from its borders. The balance of power is currently emerging as the most realistic concept of international relations, although Russia and China are waiting for the moment when the inevitability of economic growth will change the balance of power in their favor.